EFFORTS TO INSTILL THE PERSONALITY OF ULUL ALBAB TO STUDENTS IN THE QURAN - Zailani Zailani; Dessy Ariani Hasibuan; Silvia Febrianti; Salmiah Nasution (Proceeding International Seminar of Islamic Studies, 2021)
UlulAlbab is an ideal human concept according to the Qur'an which we have encountered 16 times and its nature. The formulation of problems related to this writing is (1) Why are students being targeted in an effort to instill the personality of UlulAlbab?; (2) How does the school instill the personality of UlulAlbab to the students? This study aims to (1) Find out why students are the target of efforts to instill the personality of UlulAlbab; (2) Knowing the efforts of the school to instill the personality of UlulAlbab to the students. The author uses qualitative method in the form of observation and interview. Based on the survey, the reason students are targeted in an effort to instill the personality of UlulAlbab because students are one of the important assets for the nation and religion.Moreover, in the era of globalization as it is today, we often meet students who are far from the personality of UlulAlbab. The efforts made by the school in instilling the personality of UlulAlbab to students is galvanizing its students to model the personality of UlulAlbab. Keywords: Personality UlulAlbab, Students